THE OPPRESSION REMEDY—CLARIFICATIONS ON BOUNDARIES. (3rd July 2015) - Koh, Pearlie
Abstract : The impetus behind the introduction of the statutory provision was the perceived need to protect the vulnerable minority shareholder against the unfair manipulation of the majority rule. Its raison d'être is clearly personal. And, as it is an important tool in the minority shareholder's arsenal, it is necessary that the scope of its application be sufficiently wide. The provision is therefore couched in expansive terms. This has led to questions being raised as to the scope of its application. Specifically, can a shareholder attempt to vindicate corporate claims through the provision? This short paper considers this issue against the background provided by the recent Singapore Court of Appeal decision of Ng Kek Wee v Sim City Technology Ltd.